ANALISIS PENERAPAN ANCHOR BANK DAN BANK HOLDING COMPANY DI INDONESIA: SEBUAH TINJAUAN TEORITIS - Nugraha, Rahmadya (Jurnal Akuntansi AKUNESA, 2014)
After crisis in 1997, Bank Indonesia made ??some policies to create a national banking system healthy and strong. These policies were the anchor bank and bank holding company. Both anchor banks and bank holding companies had applied in other countries and have a positive impact on the development of banking in each country. This paper analyses which policy is better for the development of the national banking. Keyword: anchor bank, bank holding company, bank